DCTR U-Net: automatic segmentation algorithm for medical images of nasopharyngeal cancer in the context of deep learning - Zeng, Yan; Zeng, PengHui; Shen, ShaoDong; Liang, Wei; Li, Jun; Zhao, Zhe; Zhang, Kun; Shen, Chong (Frontiers in Oncology, 2023)
Nasopharyngeal Carcinoma (NPC) is a malignant tumor that occurs in the wall of the nasopharyngeal cavity and is prevalent in Southern China, Southeast Asia, North Africa, and the Middle East. According to studies, Nasopharyngeal Carcinoma is one of the most common malignant tumors in Hainan, China, and it has the highest incidence rate among otorhinolaryngological malignancies. We proposed a new deep learning network model to improve the segmentation accuracy of the target region of Nasopharyngeal Cancer. Our model is based on the U-Net-based network, to which we add Dilated Convolution Module, Transformer Module, and Residual Module. The new Deep Learning network model can effectively solve the problem of restricted convolutional fields of perception and achieve global and local multi-scale feature fusion. In our experiments, the proposed network was trained and validated using ten-fold cross-validation based on the records of 300 clinical patients. The results of our network were evaluated using the dice similarity coefficient (DSC) and the average symmetric surface distance (ASSD). The DSC and ASSD values are 0.852 and 0.544 mm respectively. With the effective combination of the Dilated Convolution Module, Transformer Module, and Residual Module, we significantly improved the segmentation performance of the target region of the Nasopharyngeal Carcinoma.